Changes in Social Network Size Are Associated With Cognitive Changes in the Oldest-Old - Röhr, Susanne; Löbner, Margrit; Gühne, Uta; Heser, Kathrin; Kleineidam, Luca; Pentzek, Michael; Fuchs, Angela; Eisele, Marion; Kaduszkiewicz, Hanna; König, Hans-Helmut; Brettschneider, Christian; Wiese, Birgitt; et al. (Frontiers in Psychiatry, 2020)
Social isolation is increasing in aging societies and several studies have shown a relation with worse cognition in old age. However, less is known about the association in the oldest-old (85+); the group that is at highest risk for both social isolation and dementia. Analyses were based on the longitudinal German Study on Aging, Cognition, and Dementia in Primary Care Patients (AgeCoDe) and the Study on Needs, Health Service Use, Costs and Health-related Quality of Life in a large sample of oldest-old primary care patients (AgeQualiDe), a multi-center population-based prospective cohort study. Measurements included the Lubben Social Network Scale (LSNS-6), with a score below 12 indicating social isolation, as well as the Mini-Mental Status Examination (MMSE) as an indicator of cognitive function. Dementia-free study participants (n = 942) were M = 86.4 (SD = 3.0) years old at observation onset, 68.2% were women. One third (32.3%) was socially isolated. Adjusted linear hybrid mixed effects models revealed significantly lower cognitive function in individuals with smaller social networks (β = 0.5, 95%CI = 0.3-0.7, p < .001). Moreover, changes in an individual’s social network size were significantly associated with cognitive changes over time (β = 0.2, 95%CI = 0.1-0.4, p = .003), indicating worse cognitive function with shrinking social networks. Social isolation is highly prevalent among oldest-old individuals, being a risk factor for decreases in cognitive function. Consequently, it is important to maintain a socially active lifestyle into very old age. Likewise, this calls for effective ways to prevent social isolation.